If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3+2x)=11+3x
We move all terms to the left:
2(3+2x)-(11+3x)=0
We add all the numbers together, and all the variables
2(2x+3)-(3x+11)=0
We multiply parentheses
4x-(3x+11)+6=0
We get rid of parentheses
4x-3x-11+6=0
We add all the numbers together, and all the variables
x-5=0
We move all terms containing x to the left, all other terms to the right
x=5
| 22q-88=-28+12q | | -8u-39=7(u+3) | | 3h=727-37h-10 | | 1017=r+10 | | 4(2x+3x+8)=72 | | 6(4z+2)=3(4z+4) | | -7w+3=9–8w | | 1/2(6x+4)=14 | | 2v2+15v+45=0 | | 3w-75=-54 | | 6(4z+2)=3(4z+4 | | 5(x+1)-6=4x+3 | | 7x+4=2x+64 | | -8(w+7)=-72 | | -1-7j=-10-8j | | j/2+7=12 | | 3(x-6)=9x=30 | | -1–7j=-10–8j | | 8x=2x+18= | | 3x3=12 | | 6(x+1)-9=5x+1 | | 2^(2x+2)=3^(x−44) | | 2(x+3)-4x-8=35-13 | | 4x+4=4x+36 | | 4-4(n+4)=52 | | 1/5(x+4)-8=3/5x-2 | | 2w-10=4(w-9) | | 3(x+1)-8=2x+3 | | -1.05x=9.2=-9.7 | | 2x=6=7x-14 | | 2x+6+4x-8=35-13 | | 2x+9x=19=-63 |